The Release of Monocyte-Derived Tissue Factor-Positive Microparticles Contributes to a Hypercoagulable State in Idiopathic Membranous Nephropathy - Wang, Gui Hua (J Atheroscler Thromb, 2019)
Aim: Idiopathic membranous nephropathy (IMN) is an immune-mediated inflammatory disease characterized by a high risk of thromboembolic complications. Microparticles (MPs), a type of extracellular vesicles, have procoagulant properties, especially when they display tissue factor (TF). This study aimed to investigate whether circulating TF-positive MPs contributed to the hypercoagulable state in patients with IMN. Methods: Twenty adult IMN patients and fourteen healthy subjects were included in the study. The basic indexes of a routine biochemical examination and coagulative function were determined. The plasma levels of MPs were detected by flow cytometry, and TF activity of MPs was examined using an assay kit. The plasma levels of lipopolysaccharide (LPS) were measured by an enzyme-linked immunosorbent assay. Results: Total circulating MPs were not increased in patients with IMN compared with healthy controls. Circulating CD14(+)/TF(+)MPs were significantly increased in IMN patients, but this achieved significance was not observed in CD41(+)/TF(+)MPs between the two groups. Interestingly, the circulating TF-positive MPs were increased significantly. Plasma MPs TF assays revealed high procoagulant activity, which was positively associated with the D-dimer level in IMN. In addition, circulating LPS in IMN patients were significantly higher than those in the controls. Furthermore, after two hours' incubation with healthy whole blood, LPS enhanced the release of circulating TF-positive MPs and the TF activity of MPs. Conclusion: Increased circulating LPS may mediate the release of monocyte-derived TF-positive MPs, which further contributes to the hypercoagulable state in IMN patients. These findings provide an additional mechanism by which patients with IMN have a higher risk of thromboembolic complication.